Integration of Knowledge Engineering and 3D Printing for Digital Design and Manufacturing — A Case Study - Chang, Danni (2016)
Product design is more and more challenging and intellectual nowadays. To satisfy the dynamic customer requirements and improve manufacturing process, both Artificial Intelligence (AI) technique such as Knowledge-Based Systems (KBS) and product modeling technologies such as 3D printing (3DP) have attracted much research attention. Hence, it is rational to integrate KBS and 3DP for facilitating the design process. However, a design KBS often fails to generate graphical computer models of design prototype automatically after consultation sessions. Therefore, how to integrate a design KBS and a prototyping system remains as a research gap. To tackle this problem, a graphics generation method is proposed in this article. Through organizing alphanumeric outputs of the consultation session with a design KBS into parametric format, the consultation results can be directly used by Computer Aided Design (CAD) tools to generate graphical models which can be further exported into a 3DP system to produce physical objects. Based on a case study on wood head golf club design, it appears that the proposed method is promising in integrating a KBS and a 3DP system.